LITERATURE REVIEW STUDY: IN OBSERVING JOB SATISFACTION OF PHYSICAL EDUCATION TEACHERS - Joni Alpen; Danu, Muhammad Toriq Alamsyah (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
The purpose of this literature review is to review the scientific literature on physical education teacher job satisfaction research. One database (google schoolar) was used to select articles containing information on physical education teacher job satisfaction. The search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After exclusion criteria, only 10 articles were categorized. The results show that the types of research used in physical education teacher job satisfaction research are diverse, namely; quantitative, qualitative research, and descriptive. On average, the study used questionnaires and interviews in data collection. Several limitations inherent in the review have been noted. In summarizing the results of the study, it can be seen that physical education teacher job satisfaction is influenced by various variables and contexts, including language, geography, and pandemic conditions.